FILANTROPIS EVENT PESTA OLI GRATIS UNTUK MENINGKATKAN LOYALITAS PELANGGAN PADA BENGKEL RESMI SUZUKI JUANDA - Yiskayani Pakasi, Filadelfi; Wahyuni Arsyad, Annisa (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This journal discusses the philanthropy of Suzuki Juanda's official workshop, through an event called â€œPesta Oli Gratisâ€, which is held to increase customer loyalty through social media.In modern marketing in this era, companies do not focus only on selling products, but also must know about how to build a stronger relationship with customers. The purpose of this event is to attract customers' attention and engage them in a fun and rewarding way. Through these activities, Suzuki hopes to increase customer satisfaction and loyalty through positive experiences. The company can also increase its audience and improve brand awareness by utilizing social media as the main platform for promotion andÂ interaction. The impact of philanthropic activities on customer loyalty was assessed through Qualitative research. The research also looks at how social media contributes to this process.